Combined Immunoscore for Prognostic Stratification of Early Stage Non-Small-Cell Lung Cancer - Boscolo, Alice; Fortarezza, Francesco; Lunardi, Francesca; Comacchio, Giovanni; Urso, Loredana; Frega, Stefano; Menis, Jessica; Bonanno, Laura; Guarneri, Valentina; Rea, Federico; Conte, PierFranco; Calabrese, Fiorella; et al. (Frontiers in Oncology, 2020)
BACKGROUND To date, no combined immunoscore has been evaluated for prognostic stratification of early stage NSCLC. The main goal of this study was to investigate the prognostic impact of PD-L1 expression and different immune cell components (CD4+, CD8+ T-lymphocytes and CD68+ macrophages) in early stage NSCLC patients, distinguishing peritumoral (PT) and intratumoral (IT) localizations. The secondary aim was to identify a combined immunoscore to optimize the prognostic stratification of NSCLC patients. METHODS This retrospective study included surgical specimens from consecutive chemo-naive stage II-III radically resected NSCLC patients. Immunohistochemistry was carried out to evaluate PD-L1 expression and to quantify IT and PT CD4+, CD8+ T-lymphocytes and CD68+ macrophages. The impact of single marker and of a combination of multiple markers on overall survival (OS) was investigated. RESULTS Seventy-nine patients were included in the study. PD-L1 expression was associated with worse prognosis (3 years OS: 58% in high compared with 67% in low expressing tumors), even though without statistical significance. When integrating PT CD8+, CD4+ and CD68 into a combined PT-immunoscore, a significant prognostic stratification of patients was obtained and confirmed at multivariate analysis (3 years OS: 86% in patients with low PT-immunoscore vs 59% in patients with high PT-immunoscore, p=0.018). The integration of dNLR (derived neutrophils-to-lymphocyte ratio) with combined PT-immunoscore improved prognostic stratification, with longer OS in patients with low PT-immunoscore and low dNLR (p=0.002). CONCLUSIONS The combined PT-immunoscore (CD8+, CD4+ and CD68) integrated with dNLR may be a promising marker for the development of an integrated TNM-Immunoscore.